The Function Of First Language In Teaching English ToThe Eleventh Grade Of Social Students At Sman 1Banyudono In 2015/2016 Academic Year - Setyawan, Aryani; , Mauly Halwat Hikmat, Ph.D; , Hepy Adityarini, Ph.D (2016)
This study aims to describe the function of first language in teaching English and the teacher reasons of using first language in teaching English to the eleventh grade of social students at SMAN 1 Banyudono in 2015/2016 academic year. This study used descriptive qualitative method in analysing the data. The subject of this study is an English teacher to the eleventh grade of social students at SMAN 1 Banyudono. The data in the study were got from interviewing the English teacher and the teaching learning process in which the teacher involved in the eleventh grade of social students at SMAN 1 Banyudono in 2015/2016 academic year. The data source were event and respondent. The event was the teaching learning process of English subject in the eleventh grade of social students at SMAN 1 Banyudono. The respondent in this study was an English teacher of eleventh grade of social students at SMAN 1 Banyudono. The techniques of collecting were interview and observation. There were 6 prosedures in analysing the data: a) making a field note and transcribing; b) rereading; c) classifying; d) coding; e) tabulating; f) drawing conclusion. The result of this study showed 50 data and classified into 9 functions of first language: a) explaining exercise; b) giving instruction; c) managing classroom; d) giving feedback and error correction; e) checking understanding; f) translating words and sentences; g) giving comment on the students' work; h) making informal interaction to the students; i) explaining grammar rule. There were 7 reasons that influenced the teacher used first language in teaching English: a) to give instruction; b) to translate new language; c) to give individual comments to the students; d) to give feedback and error correction; e) to maintain discipline; f) to chat with learners; and g) to check comprehension.